The immunological pathogenesis of IgG4-related disease categorized by clinical characteristics - Mitsuhiro Akiyama; Waleed Alshehri; Sho Ishigaki; Koichi Saito; Yuko Kaneko (Immunological Medicine)
IgG4-related disease (IgG4-RD) is an immune disorder characterized by organ enlargement and fibrosis leading to functional impairment. Key immune cell subsets contributing to the pathogenesis of IgG4-RD include T follicular helper 2 cells (Tfh2), Tfh1, CX3CR1 + cytotoxic T cells (CX3CR1 + CTLs), Tregs and IgG4 + B cells. Tfh2 and Tregs are commonly involved in inducing IgG4 class-switching in this disease. Importantly, IgG4-RD can be classified into four clinical phenotypes based on the distribution of affected organs, with each phenotype showing different dominant immune cell subsets involved in its pathogenesis. Specifically, the clinical phenotype of retroperitoneal fibrosis/aortitis is characterized by CX3CR1 + CTLs as the dominant key immune cell subset, while Mikulicz disease with systemic involvement is dominated by Tfh2. In addition to classification based on organ distribution, IgG4-RD can also be categorized into phenotypes associated with malignancy or allergy. The malignancy phenotype is characterized by an increase in CXCR5 + CD2-double negative T cells compared to the allergy phenotype, along with a decrease in naive CD8 + T cells. Moreover, several autoantigens have been identified, and the presence of autoimmune phenotype has been revealed. Due to the pathogenicity of IgG1-type autoantibodies, Tfh1 may be important inducing IgG1 class-switching by IFNγ in autoimmune phenotype. In IgG4-RD with hypocomplementemia, activation of the complement pathway is thought to be induced by IgG1 or IgG2 antibodies, suggesting the involvement of Tfh1 in the disease pathogenesis. Therefore, elucidating the immunological features specific to each clinical characteristic is believed to lead to a deeper understanding of the pathogenesis of IgG4-RD and the discovery of novel therapeutic targets. This review provides an overview of the immunological mechanisms common to IgG4-RD as well as those specific to each clinical characteristic.